Fraud Risk Analysis Using Fraud Hexagon Model and Beneish M-Score in the Financial Report of PT Indo Listrik Nusantara Period 2021-2023 - Sari, Eko Gumaya; Cahyana (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
The purpose of this study is to analyze and identify the possibility of Fraud in the financial report of PT. Indo Listrik Nusantara. Using a mixed qualitative and quantitative methodology. The quantitative technique calculates the Beneish index ratio, while the qualitative method selects a sample of questionnaire responses from 52 respondents who are considered significant to be examined. An overall analysis of PT Indo Listrik Nusantara for the past three years, namely 2021 to 2023, revealed a risk of Fraud based on respondent responses. Additional searches and interviews revealed that the Company had double-booked on two different databases, namely internal management and taxation, which had an impact on the decline in the Company’s performance. Although activities like this often occur, the 2022 financial report with the calculation of the Beneish index ratio is an example of organized Fraud. This shows that the Company will not have a strong financial performance in 2022 because high sales figures are followed by high overall costs. The Beneish index ratio and the fraud hexagon are excellent tools for determining the risk of Fraud in a company’s financial statements.